Does casual touch counteract the effects of ostracism on fundamental human needs, emotions and behavior? - Konova, I.; Irina Konova; Arriaga, P.; Guinote, A.; Guinote, A. (XV PhD Meeting in Psychology, 2019)
Previous studies indicate that ostracism (i.e., being ignored or excluded) can lead to some detrimental social and psychological effects. Among the negative consequences of ostracism are threatened fundamental needs, lowered positive mood and decreased prosocial behavior. Some of these effects can be diminished, if individuals have an opportunity to experience social inclusion just after the ostracism episode. This study sought to examine for the first time whether an interpersonal touch, as a nonverbal sign of social inclusion and communion, can counteract the impact of ostracism. The experiment had a 2 (inclusion vs. ostracism) x 2 (touch vs. no touch) between- participants factorial design. Ostracism was manipulated by using the Cyberball paradigm, a virtual ball-tossing game. After the ostracism manipulation the researcher briefly touched or not participants' upper arm in a casual way. Next, participants were asked to fill out several forms including the Need Threat Scale, the Positive and Negative Affect Schedule, a questionnaire evaluating the researcher and a measure of helping behavior. The results demonstrated the role that interpersonal touch plays in mitigating the consequences of ostracism, by increasing self- esteem and positive emotions.